The Effects of Industry Specialization on Audit Risk Assessments and Audit-Planning Decisions - Low, Kin-Yew (The Accounting Review, 2004)
This study investigates the effects of industry specialization on auditors' risk assessments and audit-planning decisions. In an experiment, auditors from different industry specializations complete a hypothetical audit case set in a specific (bank) industry, which creates either a match or a mismatch between the auditors' industry specialization and the hypothetical client's industry. Furthermore, I manipulate the industry-specific case information to achieve differential audit risk levels. I also provide the auditors with a set of preliminary audit procedures and a constrained time budget. I find that the auditors' knowledge of the client's industry improves their audit risk assessments and directly influences the nature and the perceived quality of their audit-planning decisions. In addition, the auditors' knowledge of the client's industry moderates the sensitivity of the auditors' planning decisions to their audit risk assessments.